Zjawisko przedwczesnego kończenia nauki i jego ograniczanie - Madalińska-Michalak, Joanna (Wydawnictwo Naukowe UAM, 2017)
The article discusses the phenomenon of early school leaving, the scale of this phenomenon in Europe, the ways of conducting research on it and its reduction. ESL is caused by a combination of individual, educational and socio-economic factors. Therefore, the article points out that any measures taken to tackle the phenomenon of ESL, focused on prevention, intervention or compensation, must take into account the specific situation of the country and the region. There is no single solution that would be appropriate in all situations and everywhere. The results presented have been achieved within an international educational project: “ESSE – Early School Leaving & Second ChanceEducation”, supported by the European Commission within the Lifelong Learning Programme and by Poland’s Ministry of Science and Higher Education.
Phenomenon of Early School Leaving and Its Reduction
Keywords: early school leaving phenomenon; ESL indicator; early adulthood; improvement of quality of education; ESSE project